Yahoo Web Search

  1. Sort by

  1. ...by 3(k-1) to get rid of fractions 3k(k-1) = k+15 ==> expand the LHS 3k^2-3k = k+15 ==> move everything to the LHS 3k^2-4k-15=0 actually...

    3 Answers · Science & Mathematics · 21/07/2007

  2. ... / (EI) ==> M = y'' EI Looking at the LHS of the Beam P/2 ======= P ======= P/2 | ------ x...

    1 Answers · Science & Mathematics · 16/01/2014

  3. ... should check this back to see that it satisfies the differential equation (LHS) but no time I'm afraid! We now have to find any particular solution...

    2 Answers · Science & Mathematics · 19/03/2013

  4. y1'(t) = 0 y2'(t) = 3(t-t0)^2 Then, for y1: LHS: y'(t) = 0 RHS: 3y^(2/3) = 3(0)^(2/3) = 0 ✓ And for y2: LHS: y'(t) = 3(t-0)^2 = 3t^2 RHS: 3y^(2/3) = 3[(t-0)^3]^(2/3) = 3t^2 ✓

    1 Answers · Science & Mathematics · 30/09/2009

  5. ..., so the only vertical forces in the cut members in the LHS of the truss are in CG. Then the vertical load in CG...

    1 Answers · Science & Mathematics · 31/01/2012

  6. ...91 is a transformation of Eqn 2-88, using 2-89 to replace the LHS and using 2.90 to replace the RHS of 2-88. Eqn 2-92 ...

    1 Answers · Science & Mathematics · 26/05/2013

  7. ...of the RHS is obviously ln(x) + C. Integral of the LHS looks tough, trying Wolfram Integrator if you'...

    1 Answers · Science & Mathematics · 03/07/2013

  8. 1. Simplify the given equation. 2. Move all the unknowns(usually the subject) on your LHS and the rest of the known values on the RHS 3. Equate them to get the answer.

    1 Answers · Science & Mathematics · 18/03/2014

  9. ...: tan² θ cos² θ + cot² θ sin²θ = 1 LHS = (sin²θ/cos²θ) × cos² θ+ (cos²θ/sinθ²...

    1 Answers · Science & Mathematics · 01/10/2013

  10. r(t) = e^-t costi + e^-t sintj + e^-tk This shows that point (x, y, z) is parametrically (e^-t cost, e^-t sint, e^-t) LHS= z^2= e^2t RHS= x^2 + y^2= e^2t( cos^2t + sin^2t )= e^2t So vector lies on cone

    1 Answers · Science & Mathematics · 25/09/2014

  1. Try asking your question on Yahoo Answers